Safeguarding National Values and Truths: Nurturing an Information Culture among Future History Teachers - Siddikov, Ilyasjon (Universitas Muhammadiyah Sidoarjo, 2023)
The aim of this study is to investigate the importance of developing an information culture among future history teachers, particularly in terms of safeguarding national values and truths in the face of information threats and attacks. A qualitative research approach was employed to gather and analyze data from various sources, including academic literature, interviews with history educators, and online surveys. The findings of this study reveal that the formation of an information culture among future history teachers is crucial in promoting historical accuracy and preventing the spread of misinformation and propaganda. In particular, it is vital to identify and address the sources of external attacks on information security to protect national values and ancient traditions. The implications of this study suggest that a stronger emphasis on information literacy and critical thinking skills should be integrated into history teacher education programs, to better equip future educators in navigating the complexities of historical truths and falsehoods in the modern information age. Highlight The study emphasizes the importance of developing an information culture among future history teachers to safeguard national values and truths. Findings reveal that information literacy and critical thinking skills are essential in promoting historical accuracy and preventing the spread of misinformation and propaganda. The study suggests the need to integrate these skills into history teacher education programs to better equip future educators in navigating the complexities of historical truths and falsehoods in the modern information age.